'Eleven different names, one practice': towards a phenomenology of translation. (4th May 2021) - Marais, Kobus
ABSTRACT: This article challenges the notion that etymological differences in nomenclature for translation practices across the world is meaningful. It presents data from South Africa that show that the different languages in South Africa use words with diverse etymology but that these differences are not reflected in translation practice. Having made the point that etymological differences do not necessarily provide insight into translation practice, the article then proceeds to suggest a scholarly definition of translation, based on Peircean semiotics. The article further contributes to the conceptualisation of a philosophy of translation by arguing that the biosemiotic theory of translation, based on Peircean semiotics (proposed elsewhere by the author), indeed constitutes a phenomenology of translation.